Scientific motivations and future directions of whole atmosphere modeling - Pedatella, N. M. (Frontiers in Astronomy and Space Sciences, 2022)
The recent development of whole atmosphere models that extend from the surface to the upper thermosphere represents a significant advance in modeling capabilities of the ionosphere-thermosphere. Whole atmosphere models have had an especially important influence on understanding the role of terrestrial weather on generating variability in the ionosphere-thermosphere. This paper provides an overview of the scientific motivations and contributions made by whole atmosphere modeling. This is followed by a discussion of future directions in whole atmosphere modeling and the science that they will enable.